It’s about time! Exploring time allocation patterns of adults with lower literacy skills on a digital assessment - Kaldes, Gal; Tighe, Elizabeth L.; He, Qiwei (Frontiers in Psychology, 2024)
This study leverages process data from the Program for the International Assessment of Adult Competencies (PIAAC) to examine adult respondents’ time allocation patterns (time to first action, time for last action, total time) across all levels of proficiency on nine digital literacy items that were considered the easiest and most appropriate for adults with lower literacy skills (Testlet L11). Additionally, cluster analysis was used to examine groups of time allocation within the group of adults who scored lower on the digital literacy assessment, and whether individual (e.g., race/ethnicity, age, employment) and contextual (e.g., information communication and technology [ICT], reading, numeracy, and writing skills-use at home) factors predicted these groups. Results indicated that adults with lower reading proficiencies spent significantly less time on many of the items across all timing variables than adults who demonstrated higher literacy proficiencies. Cluster analysis revealed distinct patterns among adults exhibiting lower proficiency levels, delineating two specific groups defined by their time allocation – one group (Cluster 1) exhibited significantly longer engagement times, whereas the other group (Cluster 2) demonstrated comparatively shorter durations. Finally, we found that adults who had relatively higher literacy performance, higher self-reported engagement in writing skills at home, reported a learning disability, were older, unemployed, and self-identified as Black, had a higher probability of Cluster 1 membership (spending more time). These findings offer educational insights for enhancing the performance of adults with lower literacy skills on digital literacy assessments.